2021
DOI: 10.1038/s41420-020-00379-8
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus infection induces endoplasmic reticulum stress and apoptosis in placental trophoblasts

Abstract: Zika virus (ZIKV) infection to a pregnant woman can be vertically transmitted to the fetus via the placenta leading to Congenital Zika syndrome. This is characterized by microcephaly, retinal defects, and intrauterine growth retardation. ZIKV induces placental trophoblast apoptosis leading to severe abnormalities in the growth and development of the fetus. However, the molecular mechanism behind ZIKV-induced apoptosis in placental trophoblasts remains unclear. We hypothesize that ZIKV infection induces endopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 82 publications
1
25
0
Order By: Relevance
“…Interestingly, ZIKV infection is related to pro-inflammatory cytokine expression and apoptosis in placental explants, thus we propose that human placental explants can be used as a model for studying ZIKV infection in vitro (Ribeiro et al, 2018). Moreover, the mechanism of ZIKV-induced placental trophoblast apoptosis involves the activation of ER stress and JNK activation, and the inhibition of JNK dramatically prevents ZIKV-induced trophoblast apoptosis (Muthuraj et al, 2021).…”
Section: Zikv Regulation Of Apoptosismentioning
confidence: 94%
“…Interestingly, ZIKV infection is related to pro-inflammatory cytokine expression and apoptosis in placental explants, thus we propose that human placental explants can be used as a model for studying ZIKV infection in vitro (Ribeiro et al, 2018). Moreover, the mechanism of ZIKV-induced placental trophoblast apoptosis involves the activation of ER stress and JNK activation, and the inhibition of JNK dramatically prevents ZIKV-induced trophoblast apoptosis (Muthuraj et al, 2021).…”
Section: Zikv Regulation Of Apoptosismentioning
confidence: 94%
“…Zika virus is known to cause apoptosis via sustained ER stress in the trophoblasts [30]. The principal findings of the present study are: (1) palmitoleate, an omega-7 monounsaturated fatty acid significantly reduces ZIKV infection-induced trophoblast apoptosis; (2) treatment of palmitoleate interferes with ZIKV replication in trophoblasts; (3) palmitoleate treatment after ZIKV infection in trophoblasts downregulates the activation of ER stress markers that occur due to viral protein overload; and (4) palmitate, a saturated fatty acid with similar carbon structure to palmitoleate augments cell death in ZIKV-infected trophoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…We earlier demonstrated that ZIKV infection of trophoblasts induces an increase in the levels of C/EBP homologous protein (CHOP) mRNA and Spliced X box associated protein-1 (XBP1) mRNA, which are key markers of ER stress [30]. We assessed the activation of ER stress markers, namely CHOP mRNA expression and XBP1 gene splicing with palmitoleate or palmitate treatment to ZIKV-infected JEG-3 cells.…”
Section: Palmitoleate Protects Against Zikv-induced Endoplasmic Reticulum (Er) Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of congenital Zika infection is highest early in pregnancy (first trimester) [ 113 ]. Infants infected with ZKV develop important damage on various tissues including the central nervous system; this results in intrauterine growth retardation with stillbirths, and increased infant mortality 2 to 3 days postpartum [ 114 ]. Zika RNA has also been found in breast milk of ZKV-infected mothers [ 115 ].…”
Section: Maternal Nutrition and Lifestyle For Healthy Pregnanciesmentioning
confidence: 99%